Response surface based optimization of system variables for liquid chromatographic analysis of candesartan cilexetil - Jagdish V. Manwar; Snehal S. Vispute; Dipak D. Kumbhar; Rahul S. Manmode; Ravindra L. Bakal; Rajesh G. Jadhao; Shreyas D. Jogdand (Journal of Taibah University for Science, 2017)
A statistical optimization method was successfully employed to study the effect of system variables on the chromatographic analysis of candesartan cilexetil. The effect of simultaneously varying the flow rate, temperature and concentration of acetonitrile in the mobile phase in water (0.05% O-phosphoric acid (0.05% OPA)) was studied to optimize the method to obtain excellent chromatographic responses. The optimum conditions were determined with the help of response surface methodology (RSM) using Plackett–Burman designs. From the response surface graphs, the optimum regions were selected to be −1, +1 and +1 for flow rate (0.8 ml/min), temperature (25 °C) and concentration of acetonitrile in water (0.05% OPA) (80%, v/v), respectively. Pareto ranking indicated that the most important variable affecting the selected responses was temperature. Linearity was found in the range of 10 of 50 μg/ml, with a significantly high correlation coefficient (r2 = 0.9989). The limits of detection and quantitation were 0.12 and 0.33 μg/ml, respectively. The developed method was validated for accuracy, precision, linearity, range, and specificity. The method was successfully used to analyze a tablet formulation to assess the chromatographic performance, and it was found to be 99.03%, with a standard deviation of ±0.04.